Co‐Occurrence and Clustering of Sedentary Behaviors, Diet, Sugar‐Sweetened Beverages, and Alcohol Intake Among Adolescents and Adults: The Latin American Nutrition and Health Study (Elans) - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Poor diet, sedentary behaviors, sugar‐sweetened beverages (SSB) and alcohol intake seem to co‐exist in complex ways that are not well understood. The aim of this study was to provide an understanding of the extent to which unhealthy behaviors cluster in eight Latin America countries. A secondary aim was to identify socio‐demographic characteristics associated with these behaviors by country. Data from adolescents and adults from the “Latin American Health and Nutrition Study” was used and the prevalence of screen‐time, occupational and transportation–sedentary time, socializing with friends, poor diet, SSB and alcohol intake, alone and in combination, were identified. The eight Latin America (LA) countries added to analyses were: Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela. Logistic regression was used to estimate associations between ≥2 behaviors clustering, socio‐demographics and weight status. Among 9218 individuals, the most prevalent behaviors were transportation and occupation–sedentary time, SSB and alcohol intake. Younger, female, married/living with a partner, low and middle‐income and obese individuals had higher chances for these clustering behaviors. These results provide a multi-country level of understanding of the extent to which behaviors co‐occur in the LA population. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.